The Effect of Exposure to Microplastic Polystyrene (PS) in Feed on the Haematology of Tilapia (Oreochromis niloticus) - Saomadia, Baiq Triska; Setyono, Bagus Dwi Hari; Affandi, Rangga Idris (Journal of Fish Health, 2024)
Indonesia is one of the countries that has the largest archipelago area in the world. Indonesia's vast territorial waters also present major challenges in terms of environmental management. One problem that is getting worse is plastic waste. Over time, plastic waste scattered in the environment will degrade into small particles which are usually called microplastics. Tilapia (Oreochromis niloticus) is one of the economically and ecologically important freshwater fish species. This fish is not only an important source of protein for humans, but also plays a role in the balance of the marine ecosystem. Exposure to microplastics in fish can occur in various ways, including through contaminated feed. The aim of this study was to determine the effect of exposure to polystyrene (PS) microplastics in feed on the blood profile of tilapia (Oreochromis niloticus). The treatments given were P1 without exposure to microplastics, P2 with 0.01 mg/0.75 g, P3 with 0.1 mg/0.75 g, and P4 with 1 mg/0.75 g. The parameters measured in the study were blood profiles, including hematocrit, hemoglobin, erythrocytes, leukocytes, leukocyte differential and survival rate. The results obtained in this study were that hematocrit levels and survival rates had an effect on fish growth, while erythrocyte, leukocyte and leukocyte differential values had no significant effect on the blood profile of Nile fish exposed to polystyrene microplastics.